Establishing the fluorescent amyloid ligand h-FTAA for studying human tissues with systemic and localized amyloid. (2nd April 2016) - Sjölander, Daniel; Röcken, Christoph; Westermark, Per; Westermark, Gunilla T.; Nilsson, K. Peter R.; Hammarström, Per
Abstract: Rapid and accurate detection of amyloid deposits in routine surgical pathology settings are of great importance. The use of fluorescence microscopy in combination with appropriate amyloid specific dyes is very promising in this regard. Here we report that a luminescent conjugated oligothiophene, h-FTAA, rapidly and with high sensitivity and selectivity detects amyloid deposits in verified clinical samples from systemic amyloidosis patients with AA, AL and ATTR types; as well as in tissues laden with localized amyloidosis of AANF, AIAPP and ASem1 type. The probe h-FTAA emitted yellow red fluorescence on binding to amyloid deposits, whereas no apparent staining was observed in surrounding tissue. The only functional structure stained with h-FTAA showing the amyloidotypic fluorescence spectrum was Paneth cell granules in intestine. Screening of 114 amyloid containing tissues derived from 107 verified (Congo red birefringence and/or immunohistochemistry) amyloidosis patients revealed complete correlation between h-FTAA and Congo red fluorescence (107/107, 100% sensitivity). The majority of Congo red negative control cases (27 of 32, 85% specificity) were negative with h-FTAA. Small Congo red negative aggregates in kidney, liver, pancreas and duodenum were found by h-FTAA fluorescence in five control patients aged 72–83 years suffering from diverse diseases. The clinical significance of these false-positive lesions is currently not known. Because h-FTAA fluorescence is one magnitude brighter than Congo red and as the staining is performed four magnitudes lower than the concentration of dye, we believe that these inclusions are beyond detection by Congo red. We conclude that h-FTAA is a fluorescent hypersensitive, rapid and powerful tool for identifying amyloid deposits in tissue sections. Use of h-FTAA can be exploited as a rapid complementary technique for accurate detection of amyloid in routine surgical pathology settings. Our results also implicate the potential of the technique for detection of prodromal amyloidosis as well as for discovery of new amyloid-like protein aggregates in humans.